ANALISIS KEMAMPUAN PEMECAHAN MASALAH MAHASISWA PADA MATERI INDUKSI MATEMATIKA - Zulkarnain, Zulkarnain; Fathinah, Atika Luthfiyatil (IAIN Pontianak, 2023)
This research aims to determine students' mathematical problem solving abilities in mathematical induction material. The research subjects used were students of the third semester study program of Tadris Mathematics, FTIK, IAIN Pontianak for the 2023/2024 academic year. This research uses quantitative descriptive methods and research data uses student worksheets on the Mid-Semester Examination (UTS) for the 2023/2024 mathematics induction number theory course. The results obtained showed that the level of students' problem solving abilities on mathematical induction material was in the form of a series, namely: (1) understanding problems in the very high category (82.23%); (2) planning a high category solution (67.34%); (3) resolving high category problems (62.11%) and rechecking low category problems (30.12%). Meanwhile, the level of students' problem solving abilities on mathematics induction material in the form of equations, the overall indicators are in the low category, namely: (1) understanding the problem (33.24%); (2) planning completion (34.45%); (3) solving problems (30.34%) and (4) checking again (37.22%). Therefore, specifically for the induction of mathematical material in the form of equations, it is necessary to change the learning concept in the next school year in order to improve students' problem solving abilities.